Hysteresis behaviour of sensitivity in Ch4 detection in air using Sno2 with Pd as sensitizing additive - Dennis, John Ojur; Abd. Karim, Mohd. Mustamam; Ibrahim, Zuhairi; Saidin, Mohd. Khairi (Penerbit UTM Press, 2002)
The sensitivity of SnO2 with Pd as an additive showed a hysteresis behaviour when measurement was carried out as the operating temperature is increasing compared to measurement with decreasing temperature. The sensitivities of the samples that were calculated at the various operating temperatures from 200Â°C to 430Â°C were found to be higher when measuring with decreasing temperature. This observed hysteresis in sensitivity is discussed in terms of the type of oxygen species adsorbed on the SnO2 surface.